The Effects of Electronic Word of Mouth (Ewom) and Brand Ambassador Concerning Consumer Purchase Decisions - Nofrianti, Lena; Ghaefira Nur Fatimah (EDU PARTNER INDONESIA, 2024)
The increasing competition in the beauty industry has made effective marketing strategies critical, particularly for products like Scarlett Whitening. This study examines the influence of two key variables Brand Ambassador (X1) and Electronic Word of Mouth (e-WOM) on consumer purchase decisions. The research problem focuses on understanding which marketing method better drives purchasing decisions. Using a quantitative approach, data was collected and analyzed to assess the impact of these variables. The findings reveal that while Brand Ambassadors have minimal influence on consumer purchase decisions, e-WOM significantly and positively impacts purchasing behavior. Combined, both factors account for 69.2% of the variation in consumer decisions. The results highlight that e-WOM is more effective than Brand Ambassadors in influencing buyers in the beauty industry. This study concludes that leveraging e-WOM-based marketing strategies can better guide consumers in making informed purchasing choices, providing a valuable reference for businesses aiming to enhance their marketing effectiveness in the competitive beauty product market.